The need of pharmacovigilance activities in Yemen - Alshakka, Mohamed Ahmed; Al-Shami, Abdulkareem Mohammed; Mohamed Ibrahim, Mohamed Izham; Hassali, Mohamed Izmi; Alresheedy, Alian; Altamimi, Saleh; Algfrl, Saleh (Global Journals Inc., 2014)
Adverse drug reactions, medication errors and other drug-related problems are the leading causes of hospitallisation and are associated with a huge economic burden and significant human suffering. This serious issue of medication therapy also contributes to morbidity and mortality. At present, the monitoring of adverse drug reactions was started in Yemen by establishing a pharmacovigilance centre in 2011. Till now there is no published information about its work , number of reports and how they process it. The country and public are facing with many safety problems related to drug smuggling, counterfeit drugs, improper and irrational use of drugs, importation of unnecessary drugs and medical errors. Therefore, it is necessary to make serious steps and active regulations in Yemen to ensure patients and public safety in relation to medicines use.